2015
DOI: 10.13075/ijomeh.1896.00597
|View full text |Cite
|
Sign up to set email alerts
|

Pleural mesothelioma: Case-report of uncommon occupational asbestos exposure in a small furniture industry

Abstract: The relationship between asbestos exposure and malignant mesothelioma is no longer disputed, although it is not always easy to trace past occupational exposure. This report describes a case of uncommon asbestos exposure of a small furniture industry worker, who subsequently died of pleural malignant mesothelioma, to stress the crucial importance of a full reconstruction of the occupational history, both for legal and compensation purposes. Sarcomatoid pleural mesothelioma was diagnosed in a 70-year-old man, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Entre as DRAs que acometeram os trabalhadores desta pesquisa, destaca-se a prevalência do MM, doença com rápida evolução, cujo período de latência depende do tempo de exposição, podendo ter uma latência de até 50 anos 21,27,47,48 . Observou-se, em um estudo realizado na Bélgica em 2015, que a mortalidade por MM foi maior entre os trabalhadores manuais em indústrias de amianto 22 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Entre as DRAs que acometeram os trabalhadores desta pesquisa, destaca-se a prevalência do MM, doença com rápida evolução, cujo período de latência depende do tempo de exposição, podendo ter uma latência de até 50 anos 21,27,47,48 . Observou-se, em um estudo realizado na Bélgica em 2015, que a mortalidade por MM foi maior entre os trabalhadores manuais em indústrias de amianto 22 .…”
Section: Discussionunclassified
“…Of the ARDs that affect the workers included in this research, it is worth noting the prevalence of MM, a rapidly evolving disease whose period of latency depends on time of exposure and may reach up to 50 years. 21 , 27 , 47 , 48 A study conducted in Belgium in 2015 showed that mortality for MM was higher among blue-collar asbestos workers. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Mesothelioma is a malignancy which is intimately associated with exposure to asbestos [1][2][3][4] . It may occur in the pleura or peritoneum, with the latter being less frequent 5 .…”
Section: Introductionmentioning
confidence: 99%
“…While improving the pension service, it is not only to pay attention to the material conditions created by the society or family, but also to ignore the mental health of the elderly. Humanized care is the ultimate goal of intelligent pension [18].…”
Section: Introductionmentioning
confidence: 99%